The educational values included in the book “Refining morals and purifying races” by Ibn Miskawayh (analytical study) - Alhejilan, Samar Abdullah; Alharbi, Nurah Saad; Alsaykhan, Hawadi Saleh (Journal of Educational and Psychological Sciences, 2023)
The study aimed to know the educational values included in the book “Refining morals and purifying races” by Ibn Miskawayh, by identifying the educational values included in the book “Refining morals and purifying races”, as well as reaching the most important educational concepts on which Ibn Miskawayh relied, and identifying the philosophical foundations of educational thought of Ibn Miskawayh, the researchers used the historical approach in addition to the analytical descriptive approach to reach the results of the study. The most important of them: Ibn Miskawayh’s book Refining Morals and Purifying Races is one of the most important scientific works in the field of education and is a reference for experts in the field of education. -Ibn Miskawayh launched several educational concepts on education, including discipline, correction, discipline, and politics.. - The moral, social and cognitive foundations of Ibn Miskawayh’s educational thought- The study also recommended several recommendations, as follows: - The need to pay attention to the correct education curriculum, and this is what Miskawayh was keen on, so that the educational curriculum is integrated, taking into account all human aspects. - The importance of instilling good moral values in the individual for the benefit of society.